A Review of Barriers and Disparities in Reproductive Health Services: With Special Emaphasis on Young Mothers in Pakistan (Journal of Asian Development Studies, 2026)
Reproductive health is a key part of both public health and human progress, but there’s still a huge gap between regions. Here, I’m pulling together what the research says about where things stand, focusing on the challenges young mothers face in places with limited resources—especially in Pakistan. It investigates multifaceted barriers (socio-economic, cultural and systemic) that limit access to and utilisation of essential RH services. The review highlights interactions between less-than-optimal reproductive health outcomes and other broader problems of poverty, gender inequality, and lack of female empowerment. Evidence shows that maternal mortality and morbidity are unacceptably high in Pakistan and are attributed to issues such as low rates of skilled birth attendance, unmet needs of family planning and early marriage. The findings underscore the need for targeted interventions on improving the quality, accessibility and acceptability of RH services as well as policies that enable women to make informed decisions about their sexual and reproductive life.